Population Structure and Genetic Diversity in Sweet Cassava Cultivars from Paraná, Brazil - Ortiz, Alex Henrique Tiene (2016)
The objectives of the present study were to assess the population structure and genetic diversity in traditional sweet cassava cultivars collected in “backyard” cultivations in the municipalities of Maringá, Cianorte, and Toledo, State of Paraná, Southern Brazil, using 13 SSR molecular markers. All the loci analyzed were considered polymorphic with a mean of 3.15 alleles per locus; the mean polymorphism information content (PIC) value found was 0.4598, indicating that the primers were reasonably informative and the heterozygosity amplitude observed ranged from 0.0270 (GA134) to 0.8718 (SSRY45), with a mean of 0.4762, while the mean genetic diversity obtained was 0.5407, ranging from 0.3138 (GA21) to 0.6502 (GA140). The most divergent combinations were BGM434T-BGM20M, BGM35C-BGM20M, BGM430T-BGM232M, BGM430T-BGM164M, BGM430T-BGM322M, and BGM35C-BGM164M. The analysis of population structure distributed the traditional cultivars assessed in four different groups. The analysis of molecular variance (AMOVA) estimated that 11, 15, and 74 % of the variance were between groups, between individuals within groups, and between individuals within the population as a whole, respectively. The Fis (0.170) and Fit (0.259) values indicated a number of heterozygotes present in the population under study lower than that necessary to reach the Hardy-Weinberg equilibrium. The genetic variability found among the traditional sweet cassava cultivars assessed was considered wide, and the groups that were most distant were mostly cultivars from Toledo and Maringá.